2013
DOI: 10.12717/dr.2013.17.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differences of Three Pollicipes mitella Populations Identified by PCR Analysis

Abstract: Genomic DNAs were extracted from the turtle leg (Pollicipes mitella, 1798) population of Tongyeong, Yeosu and Manjaedo located in the southern sea of Korea. The turtle leg population from Tongyeong (0.929) exhibited higher bandsharing values than did turtle leg from Manjaedo (0.852). The higher fragment sizes (>1,200 bp) are much more observed in the Yeosu population. The number of unique loci to each population and number of shared loci by the three populations, generated by PCR using 7 primers in the turtle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 11 publications
(12 reference statements)
1
39
0
Order By: Relevance
“…PCR analysis was carried out on DNA samples extracted from a total of 21 individuals using seven decamer oligonucleotides primers. DNA extraction should be carried out according to the separation and extraction methods ( Song & Yoon, 2013 ). After several washings, lysis buffer I (155 mM NH 4 Cl; 10 mM KHCO 3 ; 1 mM EDTA) was added to the samples, and the mixture tubes were gently inverted.…”
Section: Methodsmentioning
confidence: 99%
“…PCR analysis was carried out on DNA samples extracted from a total of 21 individuals using seven decamer oligonucleotides primers. DNA extraction should be carried out according to the separation and extraction methods ( Song & Yoon, 2013 ). After several washings, lysis buffer I (155 mM NH 4 Cl; 10 mM KHCO 3 ; 1 mM EDTA) was added to the samples, and the mixture tubes were gently inverted.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers studied the sizes of DNA fragments in the PCR profiles of barramundi (Lates calcarifer) (Partis & Wells, 1996), four species of the Mullidae family (Mamuris et al, 1999), the eastern Pacific yellowfin tuna (Thunnus albacares) (Diaz-Jaimes & Uribe-Alcocer, 2003), five species of Korean catfish (Silurus asotus) (Yoon & Kim, 2004), venus clam (Gomphina aequilatera) (Kim et al, 2006) and the turtle leg (Pollicipes mitella) (Song & Yoon, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Three species of fish muscle was collected in sterile tubes, placed on ice immediately, and stored under refrigeration until needed. Genomic DNA was extracted and purified under the conditions described previously (Yoon & Kim, 2004;Song & Yoon, 2013). The DNA pellets were incubation-dried for 2 hrs, held at -40°C until analysis, and then dissolved in the TE buffer (10 mM Tris- …”
Section: Methodsmentioning
confidence: 99%
“…Detailed information on genetic markers specific to lines, breeds, species, and/or geographical populations has been used for the identification and discrimination of individuals and populations, as well as hybrid pedigrees, and for molecular genetic testing (Mamuris et al, 1999;Klinbunga et al, 2000a;Nozaki et al, 2000;Yoon & Park, 2002;Kim et al, 2004;Park et al, 2005;Yoon & Kim, 2010;Yoon et al, 2012;Song & Yoon, 2013;Oh & Yoon, 2014). Accordingly, adaptations of PCR methods to the mariculture and fishing industry have been used to estimate genetic distances (GDs) among some finfish species and/or invertebrate animals from different geographical locations (Callejas & Ochando, 1998;Tassanakajon et al, 1998;Klinbunga et al, 2000b;McCormack et al, 2000;Yoon & Park, 2002;Kim et al, 2004;Park et al, 2005;Song & Yoon, 2013;Oh & Yoon, 2014). In this study, to evaluate the GDs and dissimilarities between geographical echiuran populations, clustering analysis of two Urechis spp.…”
mentioning
confidence: 99%
“…Several studies have reported the sizes of PCR fragments for black tiger shrimp (Penaeus monodon) (Tassanakajon et al, 1998), the brittle (McCormack et al, 2000), and lobster species (Park et al, 2005). Unambiguous data, resulting from variations in DNA polymorphisms, were found to be meaningful in the identification of individuals and/or populations (Tassanakajon et al, 1998;Mamuris et al, 1999;Yoon & Park, 2002;Chenyambuga et al, 2004;Kim et al, 2004;Yoon & Kim, 2010;Yoon et al, 2012;Song & Yoon, 2013).…”
mentioning
confidence: 99%